Mechanical energy on anaerobic capacity during a supramaximal treadmill running in men: Is there influence between runners and active individuals? - Zagatto, Alessandro Moura [UNESP]; González, Joel Abraham Martínez [UNESP]; de Poli, Rodrigo Araujo Bonetti [UNESP]; Barbieri, Fabio Augusto [UNESP]; Bloedow, Leonardo de los Santos; Peyré-Tartaruga, Leonardo (Wiley, 2023)
This study verified whether mechanical variables influence the anaerobic capacity outcome on treadmill running and whether these likely influences were dependent of running experience. Seventeen physical active and 18 amateur runners, males, performed a graded exercise test and constant load exhaustive running efforts at 115% of intensity associated to maximal oxygen consumption. During the constant load were determined the metabolic responses (i.e., gas exchange and blood lactate) to estimate the energetic contribution and anaerobic capacity as well as kinematic responses. The runners showed higher anaerobic capacity (16.6%; p = 0.005), but lesser time to exercise failure (−18.8%; p = 0.03) than active subjects. In addition, the stride length (21.4%; p = 0.00001), contact phase duration (−11.3%; p = 0.005), and vertical work (−29.9%; p = 0.015). For actives, the anaerobic capacity did not correlate significantly with any physiologic, kinematic, and mechanical variables and no regression model was fitted using the stepwise multiple regression, while to runners the anaerobic capacity was significantly correlated with phosphagen energetic contribution (r = 0.47; p = 0.047), external power (r = −0.51; p = 0.031), total work (r = −0.54; p = 0.020), external work (r = −0.62; p = 0.006), vertical work (r = −0.63; p = 0.008), and horizontal work (r = −0.61; p = 0.008), and the vertical work and phosphagen energetic contribution presented a coefficient of determination of 62% (p = 0.001). Based on findings, it is possible to assume that for active subjects, the mechanical variables have no influence over the anaerobic capacity, however, for experienced runners, the vertical work and phosphagen energetic contribution have relevant effect over anaerobic capacity output.
Keywords: blood lactate; excess postexercise oxygen consumption; mechanical work; non-mitochondrial metabolic pathways; physical fitness level; time to effort failure